2021
DOI: 10.1080/20009666.2020.1835297
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation in COVID-19: a single-center retrospective study

Abstract: Introduction: COVID-19 induces a pro-thrombotic state as evidenced by microvascular thrombi in the renal and pulmonary vasculature. Therapeutic anticoagulation in COVID-19 has been debated and data remain anecdotal. Hypothesis: We hypothesize that therapeutic anticoagulation is associated with a reduction in in-hospital mortality, upgrade to intensive care unit, invasive mechanical ventilation, and acute renal failure necessitating dialysis by decreasing the over-all clot burden. Methods: A retrospective cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…Among the 8318 articles initially retrieved through our literature search, 21 fulfilled the inclusion criteria and were included in our analysis [ 11 , 12 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. The PRISMA 2020 flow diagram for systematic reviews and meta-analyses study selection is presented in Supplementary File, Figure S1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 8318 articles initially retrieved through our literature search, 21 fulfilled the inclusion criteria and were included in our analysis [ 11 , 12 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. The PRISMA 2020 flow diagram for systematic reviews and meta-analyses study selection is presented in Supplementary File, Figure S1 .…”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA 2020 flow diagram for systematic reviews and meta-analyses study selection is presented in Supplementary File, Figure S1 . A total of 7 studies reported data for intermediate versus prophylactic dose [ 11 , 27 , 28 , 29 , 30 , 34 , 35 ], while 17 studies reported data for therapeutic versus prophylactic dose of thromboprophylaxis [ 12 , 23 , 24 , 25 , 26 , 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Three studies contributed data for both intermediate versus prophylactic and therapeutic versus prophylactic dose analyses [ 29 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, our study demonstrated that low-dose ASA plus ENX was associated with decreased mechanical ventilation needs. This reflects the protective and desirable effect [38].…”
Section: Discussionmentioning
confidence: 91%
“…Al conducted a retrospective cohort consisting of 176 patients admitted to the hospital for COVID-19 infection and reported that therapeutic anticoagulation was associated with a lower rate of in-hospital mortality compared to prophylactic anticoagulation (OR 3.05, 95% CI 1.15-8.10, p = 0.04). 32 Pre-print publications by the multiplatform collaborative clinical trial (ACTIV-4a [NCT04505774], REMAP-CAP [NCT02735707], ATTACC [NCT04372589]) that aimed to assess the benefit of full dose anticoagulation to treat non critically-ill or critically ill adults hospitalized for COVID-19, compared to prophylactic dosing showed that therapeutic anticoagulation had a trend toward less mortality in non-critically ill patients. 33 Moreover, therapeutic dose anticoagulation has also been shown to reduce endothelial cell lesion (p = 0.02) which could also reduce the thromboembolic risk of COVID-19, suggesting another therapeutic target for anticoagulants.…”
Section: Discussionmentioning
confidence: 99%